Kajian Aktivitas Antikanker Ekstrak Daun Gude (cajanus cajan) Terhadap Sel Kanker Kolon Secara in Vitro - Rahayu, Muji; Roosmarinto, Roosmarinto (Jurnal Teknologi Laboratorium, 2017)
Colorectal cancer is one of the five type of highest insiden in Indonesia. One of development cancer therapeutics directed to combination of chemotherapeutic agent and chemopreventive compounds. One approach to finding a chemopreventive compounds is through the exploration of natural ingredient especialy herbs. Flavonoids is group of compounds from plants that have been widely studied as anti-cancer activity. Leave of pigeonpea (Cajanus cajan) is, kind of Legumes plants rich in flavonoids among others cajanol, quercetin, luteolin, apigenin formonentin, vitexin, orientin, biochanin A, pinostrobin, dan isorhamnetin. This study aims to determine the content of chemical compounds in the methanol extract of leave pigeon pea that has anticancer activity using WiDr colorectal cancer cells with MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) method, followed by flowcytometry test. The result of the cytotoxicity test of methanol extract of pigeonpea leaves have IC50 of 307 ug/ml and with flowcytometry method showed necrosis WiDr cell.